Lung‐specific distant enhancer cis regulates expression of FOXF1 and lncRNA FENDRR. Issue 6 (6th April 2021) - Szafranski, Przemyslaw; Gambin, Tomasz; Karolak, Justyna A.; Popek, Edwina; Stankiewicz, Paweł
Abstract: The FOXF1 gene, causative for a neonatal lethal lung developmental disorder alveolar capillary dysplasia with misalignment of pulmonary veins (ACDMPV), maps 1.7 kb away from the long noncoding RNA gene FENDRR on the opposite strand, suggesting they may be coregulated. Using RNA sequencing in lung tissue from ACDMPV patients with heterozygous deletions of the FOXF1 distant enhancer located 286 kb upstream, leaving FOXF1 and FENDRR intact, we have found that the FENDRR and FOXF1 expressions were reduced by approximately 75% and 50%, respectively, and were monoallelic from the intact chromosome 16q24.1. In contrast, ACDMPV patients with FOXF1 SNVs had biallelic FENDRR expression reduced by 66%–82%. Corroboratively, depletion of FOXF1 by small interfering RNA in lung fibroblasts resulted in a 50% decrease of FENDRR expression. These data indicate that FENDRR expression in the lungs is regulated both in cis by the FOXF1 distant enhancer and in trans by FOXF1. Our findings are compatible with the involvement of FENDRR in FOXF1 ‐related disorders, including ACDMPV. Abstract :